Financial incentives for model change in primary health care in São Paulo municipalities - Ligia Schiavon; Mônica Martins de Oliveira; Nayara; Mariana Tarricone; Luiz Victor (Saúde e Sociedade, 2023)
This article aims to characterize financial transfers within the scope of the Primary Care Block to the municipalities of the state of São Paulo, in the period between 2011 and 2017, and its relationship with the health care model change in Primary Health Care (PHC). This is a descriptive and exploratory study, of quantitative nature and with a retrospective longitudinal section. Transfers that occurred within the scope of the Variable Primary Care Floor (Variable PCF) were analyzed, aggregated according to its link with the model change. Family Health Strategy (FHS) coverage, number of home visits, and the percentage of municipalities that adhered to the Program for Access and Quality Improvement in Primary Care (PMAQ) were also considered. The results indicate the relevance of the Incentives for model change in the financing of primary health care in the state of São Paulo, especially for small municipalities, suggesting the interest of these municipalities in implementing the proposed measures. However, there are obstacles to identifying changes in practices, thus the current health care model is not properly explained from the analyzed indicators. In conclusion, complementing the use of funding as a model change-inducing device with evaluative processes specifically aimed at consolidating comprehensive PHC is needed.